PENGARUH PERSEPSI PROFESI GURU TERHADAP MINAT MELANJUTKAN PENDIDIKAN PROFESI GURU MELALUI MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING PADA MAHASISWA PENDIDIKAN DI FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS NEGERI SURABAYA - Janah, Tarisah Syafia; Dwijayanti, Renny (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Abstract Students of the education study program at the Faculty of Economics and Business (FEB) at Surabaya State University (UNESA) are less interested in improving their teaching skills and quality so they are less interested in continuing PPG. This research aims to determine the influence of perceptions of the teaching profession on interest in continuing teacher professional education through intervening variables as intervening variables for students in the education study program at FEB UNESA. This type of research uses quantitative research. The research population was students from the education study program at FEB UNESA class of 2020. The sample used was 156 students using a proportional random sampling technique. Data collection uses questionnaires/questionnaires. The data analysis technique used is simple linear regression analysis and path analysis in this study using the SPSS version 27 program. The results of this study show that the variable perception of the teacher profession (X) has a significant effect on interest in continuing teacher professional education (Y), the variable Perception of the teacher profession (X) has a significant effect on learning motivation (Z), the learning motivation variable (Z) has a significant effect on interest in continuing professional teacher education (Y), and the perception variable of the teacher profession (X) has a significant effect on interest in continuing teacher professional education (Y) through learning motivation (Z) as an intervening variable. The findings of this research can be used as a basis for further research in the field of education where further research can explore other factors that influence interest in continuing teacher professional education.